(untitled) (Conferencea, 2024)
Our country has always been diverse with the society and culture that our history Enriches, affirms and strengthens. I will quote Jeffery M. Gluckman Quote "One race, many cultures, one place". in my opinion, This quote is completely consistent with the beginning. becau(from the quote) "many cultures", about the diversity of this country indicates. "One place" is the country in which this Differences are collected. "One race" is probably "one".